STRATEGI KOMUNIKASI KPU BALI DALAM MENINGKATKAN LITERASI INFORMASI BAGI PEMILIH PEMULA PADA PEMILU 2024 - Pranisitha, Ayu Khania; Ni Made Yuliani; I Gusti Ayu Ratna Pramesti Dasih (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Indonesian General Election Commission (KPU) has set the voting date for the 2024 Election, which is February 14, 2024. In the 2019 elections, the voter turnout rate in Bali was high, reaching 80 percent, while the proportion of 2024 voters on February 14 will reach the age of 17 to 39 years, 55 to 60 percent, 22 percent of whom are novice voters. This is a challenge for KPU Bali in order to increase voter participation, especially novice voters, by creating a communication strategy related to election information literacy to prevent disinformation through social media. Based on the background, the problem formulation is found, namely 1) How is KPU Bali's strategy in improving information literacy through digital media for beginner voters in the 2024 Election? 2) How is the information management of KPU Bali to reduce disinformation about the 2024 Election on digital media channels? 3) How is the response of novice voters in accessing information provided by the Bali KPU on the implementation of the 2024 Election? The theories used in this research are Harold D. Lasswell, New Media theory and Uses and Gratification theory. This research uses mixed method. The research was conducted at the Bali Provincial KPU office, Denpasar. Qualitative data collection techniques are observation, interviews, documentation, and literature study. While for quantitative data using an online questionnaire and calculated by the Taro Yamane formula.